2015
DOI: 10.1371/journal.pone.0124840
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid-Encoded Pgp5 Is a Significant Contributor to Chlamydia muridarum Induction of Hydrosalpinx

Abstract: We have previously shown that the plasmid-encoded Pgp3 is a major virulence factor for C. muridarum induction of hydrosalpinx. We now report that Pgp5 also plays a significant role in the development of hydrosalpinx following C. muridarum induction. Pgp5 deficiency was introduced via either in-frame deletion (CM-Δpgp5) or premature stop codon installation (CM-pgp5S). Mice infected with either CM-Δpgp5 or CM-pgp5S developed hydrosalpinges at significantly reduced levels with an incidence rate of <40% and a mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 34 publications
3
45
3
Order By: Relevance
“…The success in transforming C. muridarum [19] further enabled the evaluation of the plasmid-encoded pGPs in a female mouse hydrosalpinx/infertility induction model [79–81]. C. muridarum deficient in pGP3 either by deletion of the pgp3 gene or installation of a premature stop codon in the start region of the gene largely phenocopied the plasmid-free C. muridarum [20] although deficiency in pGP5 also reduced C. muridarum pathogenicity [82]. The failure of the pGP3-deficient C. muridarum to induce hydrosalpinx correlates with its reduced ascension to, decreased survival and attenuated induction of inflammatory infiltration in the oviduct [20].…”
Section: Pgp3 Is a Key Virulence Factor Encoded By The Plasmidmentioning
confidence: 99%
See 1 more Smart Citation
“…The success in transforming C. muridarum [19] further enabled the evaluation of the plasmid-encoded pGPs in a female mouse hydrosalpinx/infertility induction model [79–81]. C. muridarum deficient in pGP3 either by deletion of the pgp3 gene or installation of a premature stop codon in the start region of the gene largely phenocopied the plasmid-free C. muridarum [20] although deficiency in pGP5 also reduced C. muridarum pathogenicity [82]. The failure of the pGP3-deficient C. muridarum to induce hydrosalpinx correlates with its reduced ascension to, decreased survival and attenuated induction of inflammatory infiltration in the oviduct [20].…”
Section: Pgp3 Is a Key Virulence Factor Encoded By The Plasmidmentioning
confidence: 99%
“…The C. trachomatis pgp5 was as competent as C. muridarum pgp5 in suppressing the expression of the plasmid-dependent genes during C. muridarum infection, demonstrating that inhibition of the plasmid-dependent chromosomal genes is a common property of Pgp5 protein from different chlamydial species. More importantly, when pGP5-deficient C. muridarum was evaluated in mice, it displayed a partial but significant attenuation in inducing hydrosalpinx [82], suggesting that pGP5 also contributes to chlamydial pathogenicity in the mouse upper genital tract although not as robust as Pgp3 [20]. The challenge questions are how pGP5 regulates its target gene expression in chlamydial chromosome and whether the attenuated pathogenicity is caused by the increased expression of the chromosomal genes.…”
Section: The Roles Of Pgp5 and Pgp8 And Their Antisense Rnas In Chlammentioning
confidence: 99%
“…We have previously demonstrated that C. muridarum clones carrying mutations in the chromosomal gene tc0237 and/or tc0668 or plasmid gene pgp3 are significantly attenuated in inducing hydrosalpinx in the mouse upper genital tract (26)(27)(28)(29)(30). Thus, the C. muridarum chromosomal gene-encoded TC0237/TC0668 and plasmid-encoded pGP3 have been defined as genital tract virulence factors (23,31).…”
mentioning
confidence: 99%
“…Development of a C. trachomatis plasmid manipulation system and a transformation system for C. muridarum helped to reveal that plasmid-encoded Pgp3 and Pgp5 are crucial for C. muridarum induction of upper genital tract disease (17,18). Deficiency in Pgp3 or Pgp5 results in reduced ascending infection to and chronic inflammatory infiltration in the upper genital tract.…”
mentioning
confidence: 99%